Multi-environment and multi-parameter screening of stability and coating efficiency of gold nanoparticle bioconjugates in application media - Junjie Wang; Stefano Giordani; Valentina Marassi; Anna Placci; Barbara Roda; Pierluigi Reschiglian; Andrea Zattoni (Scientific Reports)
Abstract Gold nanoparticles (AuNPs) and their biocompatible conjugates find wide use as transducers in (bio)sensors and as Nano-pharmaceutics. The study of the interaction between AuNPs and proteins in representative application media helps to better understand their intrinsic behaviors. A multi-environment, multi-parameter screening strategy is proposed based on asymmetric flow field flow fractionation (AF4)-multidetector. Citrate-coated AuNPs ( AuCIT, 25.1 ± 0.2 nm) and PEG-coated AuNPs (AuPEG, 38.3 ± 0.8 nm) were employed with albumin as a model system. Attention was put in investigating the influence of Au/BSA mass ratios, that allowed to identify the yield-maximizing (1:1) and product-maximizing (2.5:1) conditions for the generation of AuNPs-protein conjugates. Furthermore, bioconjugate properties were thoroughly assessed across various saline media with different pH and ionic strengths. While AuNPs with PEG coating exhibit greater stability at high salinities, such as 30 mM, their conjugates are less stable over time. In contrast, although bare AuNPs are significantly affected by pH and salt concentration, once conjugates are formed, their stability surpasses that of the conjugates formed with AuPEG. The developed methodology can fill the vacancy of standard reference quality control (QC) procedures for bioconjugate synthesis and application in (bio)sensors and Nano-pharmaceutics, screening in a short time many combinations, easily scaling up to the semi-preparative scale or translating to different bioconjugates.